Service Quality Analysis Based on Customer Satisfaction and Customer Confidence Daarul Huda Santri Shop - Muhammad Saifur Rijal; Sudarmiatin Sudarmiatin; Agus Hermawan (Asosiasi Peneliti Manajemen Adat Indonesia, 2022)
The research objective is to describe service quality, customer satisfaction and trust; analyze the effect of service quality on customer satisfaction; analyze the effect of service quality on customer trust; analyze the effect of satisfaction on customer trust; analyze the effect of trust on customer satisfaction; analyze the effect of service quality on trust through customer satisfaction and analyze the effect of service quality on satisfaction through customer trust at Daarul Huda Santri Shop at Daarul Huda Islamic Boarding School Malang. This research uses explanatory research. The research population is all customers of the Santri Daarul Huda Store. This study used a Likert scale questionnaire which was distributed to 100 respondents. Random sampling technique is used to determine the respondents. This research concludes that in between trust and satisfaction, satisfaction factors include the suitability of expectations, interest in revisiting, willingness to recommend prioritizing related to service aspects at the Daarul Huda Santri Shop